MAKNA GARIS MIRING (/) PADA FRASA “UU/PERPPU” - Septiyani, Samriananda (DiH: Jurnal Ilmu Hukum, 2021)
AbstractArticle 22 paragraph (1) Constitution of the Republic of Indonesia Year 1945 gives the President attributive authority to determine PERPPU in compelling emergencies. The position of PERPPU is regulated in Article 7 paragraph (1) letter c of Law No. 12 of 2011 with the formulation of the phrase "UU/Perppu." The use of the slash (/) raises several interpretations, so in this study, there are two problem formulations, namely the meaning of the slash (/) and the legal implications of the use of the slash (/). This legal research is a normative study using a statutory approach, a conceptual approach, and a historical approach. Sources of standard materials used are primary, secondary, and tertiary, which are collected by the method of inventory and categorization and using the method of literature study. The analysis technique used in this research is the normative analysis technique, with legal interpretation to obtain answers and prescriptions related to the legal issues raised in this study. The results of this legal research are related to the meaning of the slash line in the phrase "UU/Perppu" in Article 7 paragraph (1) of Law No. 12 of 2011 is defined by a punctuation mark that states the alternative nature in a sentence. Judging from the hierarchy of statutory regulations, it is can detect that UU/Perppu has an equal or equal position, so it is considered similar because the contents, functions, and content of the range are the same. Second, the legal implications that arise, by equalizing the position of the contents, processes, and content of the Perppu content with the Law, all provisions regulated in the Law should also be controlling by Perppu, including the regulation of criminal conditions. Apart from that, concerning the Perppu examination, the Constitutional Court decision No. 138/PUU-VII/2009 stated that the Constitutional Court had the authority to review Perppu.Keywords: government regulation instead of law (Perppu); legal implications; slash lineAbstrakPasal 22 ayat (1) UUD NRI Tahun 1945 memasrahkan kewenangan atributif pada Presiden untuk memutuskan Perppu dalam hal ikhwal kegentingan yang mendesak. Kedudukan Perppu diatur dalam Pasal 7 ayat (1) huruf c UU No. 12-2011dengan rumusan frasa “UU/Perppu”. Penggunaan tanda baca garis miring (/) tersebut menimbulkan beberapa penafsiran, maka pada penelitian ini ada dua rumusan masalah yakni makna garis miring (/) dan implikasi hukum yang ditimbulkan terhadap penggunaan garis miring (/) tersebut. Penelitian hukum ini ialah penelitian normatif dengan memakai pendekatan peraturan perundang-undangan, konseptual, serta historis. Sumber hukum yang dipakai yakni primer, sekunder serta tersier yang dikumpulkan dengan metode inventarisasi dan kategorisasi serta menggunakan metode studi kepustakaan. Teknik analisis yang dipakai pada penelitian ini ialah teknik analisis normatif yang menggunakan metode penafsiran hukum sehingga diperoleh jawaban dan preskripsi terkait rumusan masalah yang diajukan pada penelitian ini. Hasil penelitian hukum ini, pertama terkait makna garis miring dalam frasa “UU/Perppu” pada Pasal 7 ayat (1) UU No. 12-2011diartikan bagaikan sebuah tanda baca yang menyatakan sifat alternatif dalam suatu kalimat. Dilihat dari hierarki peraturan peraturan perundang-undangan dapat diketahui jika UU/Perppu mempunyai perananan yang setara maka dianggap sejenis karena isi, fungsi serta materi muatannya adalah sama. Kedua, implikasi hukum yang ditimbulkan, dengan disamakannya kedudukan isi, fungsi, dan materi muatan Perppu dengan UU maka seluruh ketentuan yang diatur dalam UU seharusnya juga diatur dalam Perppu termasuk pengaturan ketentuan pidana. Selain itu terkait dengan pengujian Perppu, dalam putusan Mahkamah Konstitusi K No.138/PUU-VII/2009 mengungkapkan jika Mahkamah Konstitusi berwenang untuk melaksanakan pengujian terhadap Perppu.